Islamization of Thomas Paine's Secular Thought - Hamid Fahmy Zarkasyi; Asrofil Fuad; Amir Reza Kusuma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Secularism is a problem that has become a disease among Muslims so it is dangerous if the secular concept develops. Thomas Paine is a secular figure who has a written work